If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-2 + -3z) + -8v = 25 (-2 * -5 + -3z * -5) + -8v = 25 (10 + 15z) + -8v = 25 Reorder the terms: 10 + -8v + 15z = 25 Solving 10 + -8v + 15z = 25 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -8v + -10 + 15z = 25 + -10 Reorder the terms: 10 + -10 + -8v + 15z = 25 + -10 Combine like terms: 10 + -10 = 0 0 + -8v + 15z = 25 + -10 -8v + 15z = 25 + -10 Combine like terms: 25 + -10 = 15 -8v + 15z = 15 Add '-15z' to each side of the equation. -8v + 15z + -15z = 15 + -15z Combine like terms: 15z + -15z = 0 -8v + 0 = 15 + -15z -8v = 15 + -15z Divide each side by '-8'. v = -1.875 + 1.875z Simplifying v = -1.875 + 1.875z
| 23+(+20)= | | 12k+14=10k-2k-14 | | 5/6x-3+1/3x=7/24x+1/8 | | s=25+0.75 | | -9=-4+x/17 | | n+(-4)+(-6n)+(-10)= | | 3a+11=-4 | | -4p-2p+8p-15+3= | | 9(d+2)=3(d-2) | | -6(-x-7)=90 | | 1128/(-47)= | | 3x+5x=2(4+7) | | -2x-4(0.25+0.5x)=1 | | 15p+7q+5p-4q= | | (1-7i)-(1-5i)= | | 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 |